PENERAPAN EVALUASI FORMATIF DALAM PEMBELAJARAN SAINS UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Novianti, Auni Afifah; Sitanggang, Artha Uli; Kristy, Clodia; Warasi, Kristin Natalia; Saputri, Rima Melati; Manjani, Nurhudayah (Universitas Negeri Medan, 2025)
This study aims to analyze the implementation of formative evaluation in Natural Science (IPA) learning at SDN 060858 Medan and its impact on improving students’ learning outcomes. The research employed a qualitative descriptive approach to gain an in-depth understanding of how formative evaluation is applied during the learning process. Data were collected through classroom observations and literature studies. The results indicate that formative evaluation was implemented systematically through three main stages: planning, implementation, and follow-up. During the learning process, teachers applied various formative evaluation techniques such as oral questioning, simple experiments, short quizzes, written reflections, and group discussions. These activities enabled teachers to monitor students’ understanding continuously and provide immediate feedback. The findings show that formative evaluation contributes positively to students’ conceptual understanding, learning motivation, and active participation in science learning. Students became more confident in expressing their ideas and showed better comprehension of scientific concepts. In addition, formative evaluation allowed teachers to adjust instructional strategies based on students’ learning needs, making the learning process more adaptive and meaningful. Therefore, formative evaluation can be considered an effective evaluation strategy to improve the quality of science learning and students’ learning outcomes at the elementary school level.